Crecimiento inicial de Carapa guianensis Aubl. “Andiroba” a diferentes dosis de fertilización foliar en las plantaciones del CIEFOR Puerto Almendra, Loreto, Perú – 2022 - Sanchez Angulo, Paola Andrea (2024)
The research was carried out in the plantations of the Forestry Research and Teaching Center, which belongs to the Faculty of Forestry Sciences of the UNAP. Its goal was to observe the growth in height and width d e Carapa guianensis Aubl., l lamada by all as “andiroba”. To this end, the effects of different amounts of the foliar fertilizer Bayfolan were looked at: 1 %, 2 % , 3 %, and another control group with no fertilizer (0 %). The study used a method that describes, analyzes, and goes to the field. This plan is simple. Lo s results showed that the 1 % amount of Bayfolan made it grow taller, with101.87 cm height and 14.13 mm diameter. On the other hand, the dose of 2 % reached 98.69 cm in high and 13. 05 mm in diameter, while q ue l a of 3 % obtained 98.15 cm and 13.58 mm, respectively. Numerical analysis, done by Kruskal-Wallis test, indicated that different amounts of compost did not cause significant changes in tall growth. But relevant differences in diameter increase were seen, which allowed rejecting the default assumption and accepting the other one. This proves that at least one of the methods had a different effect on the increase in plant thickness.